Firenze nella prima metà dell'Ottocento La città nei documenti del Catasto Generale Toscano - Raggi, Paola (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
This volume presents the first results of the authors' research work on the community of Florence in the Catasto Generale Toscano. Activated in 1834, the Catasto Generale Toscano records real estate based, for the first time in the history of the Grand Duchy, on the topographical survey of the entire territory of the State and the description and valuation of all stable property. The cadastre is thus the ideal source for reconstructing the urban situation of Florence in the Restoration era, represented here by means of a series of cartographic elaborations and a database in geometric, functional, typological and proprietary terms. An additional cartographic series highlights the persistences and variations of the present city compared to the nineteenth-century one. The digital resources (cartographic representations and databases) can be freely consulted via the QR code on the cover or here.